'You're facing that machine but there's a human being behind it': students' affective experiences on an online doctoral programme. (2nd July 2016) - Kennedy, Eileen; Gray, Morag
Abstract: Online students use highly emotional language to describe their experiences, indicating that learners do feel a great deal online. This paper draws on Wetherell's exploration of affective practice to theorise learners' responses to the pedagogical and technological online environment. Findings of a research project that focused on two cohorts of online doctoral students are presented, including survey responses and interview data. Thematic analysis indicates that participants experienced positive and negative affects circulating around three sites of intensity: a sense of progression; community interaction and assignment feedback. However, narrative analysis of extracts from the interviews reveal a further level of complexity to the data, drawing attention to the unfinished and shifting character of these affects. The paper concludes by pointing to the implications of this research for designing the online environment in ways that will allow students to experience the full potential of online learning.